2013
DOI: 10.1063/1.4831953
|View full text |Cite
|
Sign up to set email alerts
|

Self-trapped exciton and core-valence luminescence in BaF2 nanoparticles

Abstract: The influence of the BaF 2 nanoparticle size on the intensity of the self-trapped exciton luminescence and the radiative core-valence transitions is studied by the luminescence spectroscopy methods using synchrotron radiation. The decrease of the self-trapped exciton emission intensity at energies of exciting photons in the range of optical exciton creation (h E g ) is less sensitive to the reduction of the nanoparticle sizes than in the case of band-to-band excitation, where excitons are formed by the recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
(19 reference statements)
0
9
0
4
Order By: Relevance
“…Luminescence studies in nanoparticles of uoride materials have shown that luminescence properties like excitation and emission quantum efficiency depend on the particle size. 14,36 Based on density functional theory calculations (DFT), Schmalzl showed that in BaF 2 , the band gap energy may shi due to structural changes in the crystal lattice parameters. 2 From these affirmations, we investigated, using measurements in the VUV region, the luminescence and excitation luminescence spectra of BaF 2 nanoparticles with different particle sizes produced using different hydrothermal treatment times.…”
Section: Luminescence Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Luminescence studies in nanoparticles of uoride materials have shown that luminescence properties like excitation and emission quantum efficiency depend on the particle size. 14,36 Based on density functional theory calculations (DFT), Schmalzl showed that in BaF 2 , the band gap energy may shi due to structural changes in the crystal lattice parameters. 2 From these affirmations, we investigated, using measurements in the VUV region, the luminescence and excitation luminescence spectra of BaF 2 nanoparticles with different particle sizes produced using different hydrothermal treatment times.…”
Section: Luminescence Analysismentioning
confidence: 99%
“…This behavior was also predicted for BaF 2 (ref. 14) and CaF 2 (ref. 36) nanoparticles, respectively.…”
Section: Luminescence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Якщо розмiр наночастинок а менший за довжину термалiзацiї електронiв l e,th (а < l e,th ), то вiльнi електрони можуть безвипромiнювально рекомбiнувати на поверхневих дефектах або вилiтати за межi наночастинки i не брати участi в люмiнесцентних процесах усерединi наночастинки. За таких умов рекомбiнацiйна люмiнесценцiя буде iстотно гаситися [1,2,6,21], що i спостерiгається у випадку SrF 2 -Ce (а = 20 нм).…”
Section: а люмIнесценцiя наночастинок Srf 2 -Ce за оптичного збудженняunclassified
“…Виявилось, що розмiрний фактор є ключовим для пояснення залежностi параметрiв рекомбiнацiйної люмiнесценцiї вiд розмiрiв наночастинок. Для локалiзованих екситонiв у фторидних наночастинках продемонстровано, що суттєвим є спiввiдношення довжини термалiзацiї електрона та розмiрiв наночастинок [1][2][3][4]. Зокрема, дослiдження екситонної люмiнесценцiї SrF 2 показало, що її iнтенсивнiсть суттєво залежить вiд мiґрацiї екситонiв до поверхнi наночастинок, а також вiд спiввiдношення мiж довжиною термалiзацiї l th електронних збуджень та розмiрами а наночастинок.…”
unclassified